The effectiveness of employing the molecular representation strategy in the development of information Generation skills in the chemistry of second grade students in Intermediate School - Faris Yousif, Jehan (Opción, 2019)
The research aims to demonstrate the effectiveness of the molecular representa- tion strategy in developing the skills of generating information in chemistry in the second grade students. The sample chose the average female students for girls and the chosen ones, namely (46) students, The total number of students in the experimental group (23) students studied according to the strategy of molecular representation, and the total students control group (23) students studying accord- ing to the usual method. The two groups were rewarded with months of age, pre- vious information testing, and skills for generating information which consist of (28) paragraph. After the researcher completed the research experiment, the test of the skills of generating information found that the superiority of the experimental group in the development of skills to generate information on the control group taught according to the usual method.